PROGRAM OF COURSE OF PAINTING IN THE SYSTEM OF PREPARATION O OF STUDENTS OF THE SPECIALTY “FINE ART” (Pedagogy of Higher and Secondary Education, 2022)
The reference program of course of painting is given in the article, in the conditions of introduction of elements of the credit-module departmental teaching, its aims and tasks are outlined, well-organized and given descriptions of the rich in content modules, prospect of further researches in this region
Keywords: course of painting; elements of the credit-rnodule departmental teaching; rich modules in content